DISTRIBUTION, RISKS AND SOURCE APPORTIONMENT OF POLYCYCLIC AROMATIC HYDROCARBONS IN SOIL AROUND CHARCOAL PRODUCTION SITES IN SAPELE, DELTA STATE, NIGERIA - Ogwuche, Christiana E.; Ndego, Nkechi G.; Tesi, Juliet N.; Kabir, S.; Ogwuche, Emmanual A. (FUDMA JOURNAL OF SCIENCES, 2025)
The study investigated the concentrations, risks and sources of the USEPA sixteen priority polycyclic aromatic hydrocarbons (16-PAHs) in soils around charcoal production sites in Sapele, Delta State, Nigeria. A stain-less steel auger was used in collection of a total of 21 surface soil samples, the PAHs concentration were determined by a gas chromatograph equipped with mass spectrometry (GC-MS). The concentration of the soil PAHs varied from 338 to 5082 µg kg-1 for all the sites. The distribution pattern of PAHs in the soil were in the order of 3 Rings> 4 Rings> 5 Rings> 6 Rings and 2 Rings PAHs. The benzo(a)pyrene toxic equivalency (BaPTEQ) and mutagenic equivalency (BaPMEQ) values of PAHs in these soils ranged from 43.6 to 580 µg kg-1 and 45.8 to 541 µg kg-1 respectively. The ecological risk assessed using risk quotient suggested that there is low ecological risk to organisms in soil. The hazard index values indicated that there is the presence of non-carcinogenic effects on exposure to PAHs for children in 42 % of the soil samples. The total cancer risk values resulting from a child’s and an adult’s exposure of PAHs exceeded the target value of 1 × 10-6 suggesting that exposure to PAHs in these soils carries a significant risk of cancer to humans. The isomeric ratio indicated that the major sources of PAHs in these soils is high temperature combustion processes
Keywords: PAHs; Exposure risks; Sources; Soil; Charcoal production sites